Neurochemical regulation of the expression and function of glial fibrillary acidic protein in astrocytes - Li, Dongyang; Liu, Xiaoyu; Liu, Tianming; Liu, Haitao; Tong, Li; Jia, Shuwei; Wang, Yu‐Feng (Glia, 2020)
Glial fibrillary acidic protein (GFAP), a type III intermediate filament, is a marker of mature astrocytes. The expression of GFAP gene is regulated by many transcription factors (TFs), mainly Janus kinase‐2/signal transducer and activator of transcription 3 cascade and nuclear factor κ‐light‐chain‐enhancer of activated B cell signaling. GFAP expression is also modulated by protein kinase and other signaling molecules that are elicited by neuronal activity and hormones. Abnormal expression of GFAP proteins occurs in neuroinflammation, neurodegeneration, brain edema‐eliciting diseases, traumatic brain injury, psychiatric disorders and others. GFAP, mainly in α‐isoform, is the major component of cytoskeleton and the scaffold of astrocytes, which is essential for the maintenance of astrocytic structure and shape. GFAP also has highly morphological plasticity because of its quick changes in assembling and polymerizing states in response to environmental challenges. This plasticity and its corresponding cellular morphological changes endow astrocytes the functions of physical barrier between adjacent neurons and stabilizer of extracellular environment. Moreover, GFAP colocalizes and even molecularly associates with many functional molecules. This feature allows GFAP to function as a platform for direct interactions between different molecules. Last, GFAP involves transportation and localization of other functional proteins and thus serves as a protein transport guide in astrocytes. This guiding role of GFAP involves an elastic retraction and extension cytoskeletal network that couples with GFAP reassembling, transporting, and membrane protein recycling machinery. This paper reviews our current understanding of the expression and functions of GFAP as well as their regulation. Main points GFAP expression is regulated by transcription factors and enzymes at multiple levels; GFAP serves as cytoskeleton, interactive platform, and protein location guide; The guiding role of GFAP involves cellular transport and mobile machineries.